Establishing and leading a cross‐institutional partnership to integrate fundamentals of care into clinical practice, nursing education and research. (16th July 2022) - Grønkjær, Mette; Voldbjerg, Siri Lygum; Jørgensen, Lone; Kusk, Kathrine Hoffmann; Laugesen, Britt
Abstract: Aim: The aim was to describe and discuss the process of establishing and leading a cross‐institutional partnership to regain focus on and reconceptualize fundamental nursing care in clinical practice, nursing education and research in one region in Denmark. Design: A discursive paper. The case study method is used as an adapted frame for describing and discussing the establishment and strategic decisions of a cross‐institutional partnership. Data sources: This discursive paper draws on the authors' experiences with establishing a cross‐institutional partnership and related literature. Implications for nursing: The paper addresses the challenges surrounding fundamental care. Establishing cross‐institutional partnerships can contribute to a reconceptualization of fundamental care and initiate discussions on what nursing care is and requires. The paper provides an example of how a cross‐institutional partnership can be established and describes and discusses the opportunities and challenges in doing so. Conclusion: A key step in the process of establishing a partnership is to actively involve key stakeholders and stimulate their commitment to investing time and resources in the partnership. This requires commitment, clear strategic direction and leadership. Another key step is engaging and informing executive management leaders, and continuously nurture their interest. Impact: The paper aims to inform clinicians, educators, nursing leaders, researchers and policy makers on how to organize a formal partnership structured around a strategic research, development and implementation programme where the focal point of the collaboration is improving nursing care by integrating the conceptual FoC framework. No patient or public contribution: Patients, service users, caregivers or members of the public were not involved in this study as it is a discursive paper based on the authors' experiences and relevant literature.